INTEGRATED LAW ENFORCEMENT (GAKKUMDU) IN MANAGING GENERAL ELECTIONS IN INDONESIA - Ridwan Arifin (Madani Legal Review, 2019)
The number of general elections in Indonesia, such as in regional head elections, leagislative elections and in the election of president and vice president. In general elections, the president and vice president are often referred to as legislative elections, while the head of the region itself has the title, namely regional head elections only. The proverb says that where there is a rule there will be an offense. Therefore, to avoid any undesirable things, an improvement is needed to deal with this. In order to avoid fraud, in the improvement there is certainly an institution that regulates, namely from the law apparatus, as an apparatus in law enforcement is required to be able to ensure the existence of violations in the implementation of elections only because solely to enforce integrated law. In fact, the general election is always interesting so that it can be investigated, which is contained in the rules, implementation, and in the participants and the community. It certainly determines the success of the general election. If the rules are already felt or considered to be good in its implementation without capable law enforcement so that it will be difficult also in its realization. Good rules and good law enforcers also cannot maximize if the people themselves are ignorant and do not care about existing regulations. So, order between the three of them bound each other. In general elections it does not only involve one or two people, but requires a lot of people, so that the community is required to participate in issuing their opinions. But with so many parties participating in the election, there were many violations of the implementation, for example in 2014, where there were still many violations in general elections. Whereas at that time there was a socialization of the implementation of the general election which was socialized by the KPU and Bawaslu, not only socialization but also from the Bawaslu and its staff who participated in efforts to prevent the occurrence of violations in general elections. Although in the end socialization in prevention still cannot reduce the number of violations that exist. In dealing with this problem the creation of a system can reduce violations during the election, namely the process of synergy of Gakkumdu with the aim of realizing democratic elections in 2019 in the hope that it can provide the effect of clarity and change in carrying out general elections